Monstrous femininity in kazakh folklore: delineating normative and transgressive womanhood - Karazhanova, Inzhuna (Nazarbayev University School of Sciences and Humanities, 2016)
Representations of the feminine as monstrous can be found in any type of narrative from ancient mythology to modern video games. Witches, succubi, female vampires, sirens, furies, mermaids, possessed women, ghost women, etc. represent the female body and womanhood as Other, grotesque and abject, as well as demonise women who live in transgression to normative constraints of a patriarchal society. This work looks at the images of the monstrous-feminine within the Kazakh fairy tale: Zhalmauyz Kempir, Zheztyrnaq and Albasty—and argues that how these characters are presented, situated and treated in their narratives can tell us what is deemed acceptable and what is considered as violation of the established gender order. Through examining these characters, the conditions for the different representations and roles they inhabit, as well as comparing them to idealised positive heroines, this work seeks to identify how femininity and womanhood are represented in Kazakh folklore, and what those representations can tell us about gender roles, relations, and attitudes to female desire, power, autonomy and transgression of social norms.
Образы женщин-монстров в казахском фольклоре: очерчивая границы нормативной и трансгрессивной женственности
Қазақ фольклорындағы құбыжық әйел бейнесі: қалыпты және қалыптан тыс әйелдікті сүреттеу
Keywords: kazakh folklore; monstrous femininity; transgressive womanhood; образы женщин-монстров; казахский фольклор; трансгрессивная женственность; қазақ фольклор; құбыжық әйел бейнесі; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Literature